1997
DOI: 10.1152/ajpregu.1997.272.4.r1354
|View full text |Cite
|
Sign up to set email alerts
|

Leptin facilitates and inhibits sexual behavior in female hamsters

Abstract: Food deprivation decreases fertility in female mammals in part by inhibiting sexual behaviors. Genetically obese ob/ob mice, like food-deprived wild-type animals, are also infertile; treatment of ob/ob mice with leptin, the adipocyte-derived protein that they lack, corrects some of their reproductive deficiencies. We tested the hypothesis that leptin treatment would prevent the suppression of sexual receptivity that is caused by food deprivation in female Syrian hamsters. Instead, we found that treatment with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
34
0
2

Year Published

1999
1999
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(40 citation statements)
references
References 0 publications
4
34
0
2
Order By: Relevance
“…In addition, our results confirm the well-known effects of systemic leptin injections on food intake in Syrian hamsters (7,30,39). Leptin injections decrease daily food intake, and yet do not support a conditioned taste aversion in Syrian hamsters (7).…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…In addition, our results confirm the well-known effects of systemic leptin injections on food intake in Syrian hamsters (7,30,39). Leptin injections decrease daily food intake, and yet do not support a conditioned taste aversion in Syrian hamsters (7).…”
Section: Discussionsupporting
confidence: 80%
“…1,14,32,33,41), whereas fewer have examined the appetitive aspects of ingestion, such as the approach to food, the consumption of unpalatable substances, or foraging and hoarding (e.g., [3][4][5][6]11). Treatment with putative anorectic hormones, such as the adipocyte protein leptin, decreases the amount of food eaten in a wide variety of species, including chickens (10,12), mice (9,15,18,26), rats (34), Syrian hamsters (39), ground squirrels (25), dogs (20), sheep (16), primates (36), and marsupials (17). In many species, food deprivation results in decreased plasma concentrations of leptin, increased central release of neuropeptide Y (NPY), and increased food intake relative to that of ad libitum-fed controls (reviewed in Refs.…”
mentioning
confidence: 99%
“…Although it is known that leptin can accelerate sexual development, there is only one report on the effect of leptin with regard to sexual behavior in female hamsters [20]. Our previous study demonstrated that leptin-treated male rats ejaculated twice as much as aCSF-treated males [1].…”
Section: Discussionmentioning
confidence: 92%
“…In addition, leptin treatment cannot overcome the suppression of sexual behavior in food-deprived female hamsters (22), and in growth-retarded female rats mating behavior was often absent even after the start of normal cycles (23). At VO we did not observe any sign of first estrous and ovulation in female IUGR rats, in contrast to control rats in which VO was accompanied by estrous and ovulation, shown by vaginal smears and morphologically by corpora lutea in the ovary (24).…”
Section: Discussionmentioning
confidence: 99%